The Polygamy of Sheikh Sulaiman Arrasuli: Negotiating Religious Authority and Identity in the Matrilineal Muslim Society of Minangkabau - Armi, Mhd. Ilham; Zulkifli, Zulkifli; Nasri, Ahmad Luthfy (KURIOSITAS: Media Komunikasi Sosial dan Keagamaan, 2025)
This study analyzes how Sheikh Sulaiman Arrasuli (1871–1970) constructed his religious identity and authority through polygamous practices within the Minangkabau matrilineal system in the early 20th century. Using a qualitative-historiographical method, data were collected through documentation and written works of Sheikh Sulaiman Arrasuli. The data were analyzed using Erving Goffman's theoretical framework (social dramaturgy) and Charles Taylor's (authenticity) to reveal the process of identity negotiation. Findings indicate that the interaction between public performance and private negotiation in Sheikh Sulaiman Arrasuli's polygamous practice—with 17 wives—functioned as both a symbol of social prestige and a means of legitimizing religious authority in the public sphere (front stage). Meanwhile, in the private realm (back stage), a transformation occurred from commitment to monogamy toward polygamy as a result of negotiation between personal preferences and social expectations. The combination of Goffman's and Taylor's theoretical frameworks yields a deeper understanding of the construction of religious authority in the context of Islamic and cultural convergence. These findings offer insights into how ulama navigate public and private identities amid social change, while demonstrating the intersection of gender, religion, and culture in societies undergoing value transformation